(untitled) (Fiep Bulletin - online, 2014)
The capacity to supply oxygen in satisfactory levels to the body is one of the parameters that make possible the man the accomplishment of their daily activities with life quality. The objective of that study is of verifying the impact of 9 weeks of bed guided in light intensity is tended the base the protocol proposed by the (CDC) Center it goes Disease proposal Control and linking the of the (ACMS) American College of Sport Medicine that foresees positive answer to the components of the physical fitness in individuals in a minimum period of 16 weeks. They participated in this study, 12 volunteer’s female, participant of project of extension of the University of Extreme South Catarinense (UNESC). For obtaining of the dates regarding to the relative VO2 máx., the test of the mile was used; proposed by Rippe (1988). As instrument for obtaining of the data regarding age, Index of Corporal Mass (IMC) the protocol was used proposed by the World Organization of Health (OMS). It is corporal weigh divided by the height square (P/A ²). For treatment of the dates software Microsoft Excel was used. The Results: 1) the average of the acts is 50,4 years (+14.4), what characterizes a group of middle age; 2) in the level of physical fitness variable daily pay-training it was observed that the individuals met with weak level characterized by the IMC = 28,3 kg/m2 (+1,5 kg/m2) and VO2Max = 25,3 ml/kg.min-1 (+2,67 ml/kg.min-1); in the evaluation powder-training, it was observed that the individuals continued with weak level characterized by the variable IMC = 29,3 kg/m2 (+1,6kg/m2) and VO2Max 25,3 ml/kg.min-1 (+1,67 ml/kg.min-1), or be if he/she didn’t obtain improvements in the studied variables. Conclusion: Physical This activity from 20 you the 30 min. day, frequency volume from 5 you the 6 teamses in the week, intensity 50% you 55% of 9 maximum FC will be period of weeks of accomplished training, was not enough you have an to answer positive when related the improvement of the VO2 máx and IMC, to however will be the adhesion you an activates lifestyle the training was shown efficient.